How can practical wisdom manifest itself in five fundamental management and leadership practices?. Issue 1 (31st December 2020) - Jakubik, Maria
Abstract : Purpose: Practical wisdom (PW; phronesis), as one of the human virtues, is experiencing a renewal in the contemporary management literature. The aim of this conceptual paper is first, to explore the core practices of managers and leaders in the literature and second, to demonstrate how PW can manifest itself in these practices. Design/methodology/approach: The research follows the interpretivist research philosophy, inductive approach, qualitative method and the theory-building research strategy. The data collection method is a literature review. The practice ecosystem framework is applied to demonstrate the presence of PW in the core practices of managers and leaders. Findings: The paper proposes a practice-based paradigm of management and leadership. From the literature study, envisioning, enabling, energizing, engaging and executing as five fundamental practices are identified. Research limitations/implications: The most significant literature was selected based on decisions of the author. Therefore, it might be that important sources were overlooked. The paper proposes future research questions, and it calls for an empirical validation of the proposed conceptual model in management and leadership practices context. Practical implications: The practical implications for managers and leaders are in applying the framework developed in this paper as a tool or guidelines to cultivate PW in their practices. The paper offers implications for management education, traditional educational institutions and educational practitioners because they are the key influencers of wise thinking and actions of future managers and leaders. Originality/value: The novelty of this paper is in making explicit how the eight features of PW can manifest themselves in the everyday actions of managers and leaders. Applying the practice ecosystem framework for this purpose is an original contribution.